Flouting Maxim Used by Male and Female Characters in the “Spiderman: No Way Home” Movie Script - Ainun Dirgantara, Indra; Nugraheni, Yunita; Hardiyanti, Diana (Universitas Muhammadiyah Semarang, 2024)
Men and women tend to have different communication styles due to differences in social orientation and life experiences. Men tend to use communication to demonstrate status and solve problems, while women often use communication to build relationships and harmonize feelings. Women tend to pay more attention to interpersonal relationships and use communication to strengthen social ties. Therefore, it can be assume that women are more flouting Grice's maxims than men. The objectives of this research are to describe the types of maxims are flouted by male and female characters in the “Spiderman: No Way Home” Movie Script 2021 and describe the strategy for flouting the maxims by male and female characters in the “Spiderman: No Way Home” Movie Script 2021. The researcher's method of choice for this study was descriptive qualitative. The data in this research are utterances from both male and female characters in the script Spiderman: No Way Home. The data collection technique in this study was done by reading the film script thoroughly several times, selecting the data that contained flouting maxims, identifying the types of maxims that were flouted and the strategies used when flouting. The results showed that based on average women have flouting maxims more, 3 times, while male characters do it 2 times. The majority of maxims flouted by male are maxims of quality 18 times, while the majority of maxims flouted by female are also maxims of quality 4 times. The majority of maxim flouting strategies carried out by male are metaphor that is happened 8 times, while the majority of strategies carried out by female is irony that happened 3 times.